2016
DOI: 10.1159/000450728
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Intake, Zinc Bioavailability and Plasma Zinc in Obese Adolescents with Clinical Insulin Resistance Following Low Energy Diets

Abstract: Background: Zinc has a critical role in metabolism and growth. This study aims to determine the effects of low-energy diets differing in macronutrient composition on zinc intake, estimated zinc bioavailability (phytate:zinc molar ratio) and plasma zinc concentration and associations between zinc status and cardiometabolic markers in obese adolescents with clinical insulin resistance (IR). Methods: Eighty-seven obese adolescents (10-17 years, body mass index z-score 2.3 ± 0.37) with clinical IR were randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
1
6
0
1
Order By: Relevance
“…Several mechanistic factors have been implicated in this relationship. These include (over-)consumption of energy-rich foods high in phytate, which prevents absorption of zinc in the gut (Ho et al 2016 ) and increased excretion of zinc (Martins et al 2014 ) – note these factors may be linked. Reduced levels of serum albumin, the protein primarily responsible for binding and transporting the zinc in the circulation (Handing et al 2016 ), are associated with obesity (Mosli and Mosli 2017 ), where the plasma concentration was reported to be 38.0 g/L in individuals of normal weight and 34.6 g/L and 33.8 g/L in obese and morbidly obese individuals, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Several mechanistic factors have been implicated in this relationship. These include (over-)consumption of energy-rich foods high in phytate, which prevents absorption of zinc in the gut (Ho et al 2016 ) and increased excretion of zinc (Martins et al 2014 ) – note these factors may be linked. Reduced levels of serum albumin, the protein primarily responsible for binding and transporting the zinc in the circulation (Handing et al 2016 ), are associated with obesity (Mosli and Mosli 2017 ), where the plasma concentration was reported to be 38.0 g/L in individuals of normal weight and 34.6 g/L and 33.8 g/L in obese and morbidly obese individuals, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, no studies were found that evaluated this combination from a double burden perspective. Instead, several studies have described zinc as a positive regulator of glucose uptake in isolated adipocytes and its potential participation in insulin signalling 32–34 . In fact, some studies have reported an inverse relationship between obesity, a condition characterized by insulin resistance, and serum zinc levels 35 .…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Ho et al, [ 29 ] zinc bioavailability, serum zinc status and zinc intake were investigated in obese adolescents in two groups. It was shown that adolescents in the high-carbohydrate diet group had higher dietary phytate intake than in moderate carbohydrate-increased protein group, which also increased the phytate/zinc molar ratio significantly.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown a negative correlation with dietary carbohydrate (E%). [ 29 ] In addition, articles related to zinc sources and bioavailability are limited in the literature. There is a need for new studies and meta-analyses related to the absorption of zinc from foods.…”
Section: Discussionmentioning
confidence: 99%